STRATEGI KOMUNIKASI PEMASARAN RUMAH SAKIT MATA PEKANBARU EYE CENTER (PBEC) DALAM MEMBANGUN BRAND AWARENESS - Desy Wahyuni; Anuar Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Competition between services providing healthcare services is becoming increasingly strict, from clinics, public hospitals to specific hospitals. Eye Hospital Pekanbaru Eye Center is a private hospital that is not specialized for the eye. Visit to the PBEC eye hospital. Pekanbaru Eye Center Eye Hospital realizes the importance of marketing communication strategies to reach the public and improve the existence of hospitals by building brand awareness. This study is about the implementation of the marketing mix (7P) at the Pekanbaru Eye Hospital Center and how the Pekanbaru Eye Center's ophthalmic marketing communication strategy works by promoting brand awareness. This type of research is qualitative with a descriptive analysis presentation. The research topics were the Manager of Medical and Nursing Services, Staff Admissions, Staff Personnel, Coordinator of the Marketing and Collaboration Department, Members of the Marketing and Collaboration Department, and Eye Hospital Patients at Pekanbaru Eye Center. The collection of data is done through interviews, observation and documentation. Data analysis techniques by reducing data, collecting data, presenting data, drawing conclusions and evaluations using the technique of checking the validity of the data, namely the expansion of participation and triangulation. The results of this study indicate that the marketing communication strategy is promotional activities are carried out through advertising, namely print media, electronic media and outside media. Sales promotion is carried out by offering BPJS Health Services that offer discounts / discounts to patients. Face-to-face sales with direct interaction with the community through free socialization and eye checks, car-free day and events. Direct marketing is done via telephone and letter media. Interactive marketing is done through interaction with patients or the public via internet with media websites, Facebook and Instagram social media. Sending press releases to local newspaper media via public relations and publicity by being a mediator between internal and external parties. By Word of Mouth that is by improving the quality of service. Keywords: Marketing Communication, Pekanbaru Eye Center Eye Hospitlal, Brand Awareness